2017
DOI: 10.3996/062016-jfwm-048
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sex Ratio and Density on Fertilization Success of Intensively Cultured Endangered Woundfin

Abstract: Woundfin Plagopterus argentissimus are a small, endangered cyprinid found solely in the Virgin River across Utah, Arizona, and Nevada. As of now, only three facilities culture Woundfin for conservation propagation purposes, but there is growing concern that current extensive culture protocols are not meeting the conservation recovery goals outlined in the Virgin River Resource Management and Recovery Program. The development of alternative rearing methodology, like effective intensive culture conditions, could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…However, the study on Hemibagrus menoda by Jega et al (2018) at the Kangsha River, Netrakona, Bangladesh, found that the sex ratio of the species was female-biased (1.30:0.97), implying the non-existence of seasonality in sex distribution. Laboratory fertilization on Plagopterus argentissimus; a small, endangered cyprinid, found that a sex ratio of 1:1, 1:3, or 1:5 (female: male) will likely heighten fertilization success (Maskill et al, 2017). Results from respective studies and the Chi-square homogeneity test may suggest that T. thynnoides in the studied areas can still thrive.…”
Section: Sex Ratiomentioning
confidence: 89%
See 1 more Smart Citation
“…However, the study on Hemibagrus menoda by Jega et al (2018) at the Kangsha River, Netrakona, Bangladesh, found that the sex ratio of the species was female-biased (1.30:0.97), implying the non-existence of seasonality in sex distribution. Laboratory fertilization on Plagopterus argentissimus; a small, endangered cyprinid, found that a sex ratio of 1:1, 1:3, or 1:5 (female: male) will likely heighten fertilization success (Maskill et al, 2017). Results from respective studies and the Chi-square homogeneity test may suggest that T. thynnoides in the studied areas can still thrive.…”
Section: Sex Ratiomentioning
confidence: 89%
“…In fishery management practices, estimation of fish sex ratio (i.e., ready-to-mate females to ready-tomate males or vice versa (de Jong et al, 2009;Maskill et al, 2017) may assist in determining whether the population is in a standard or abnormal condition. A healthy fish population in its natural habitat usually has a sex ratio of 1:1 (Neves et al, 2020).…”
Section: Sex Ratiomentioning
confidence: 99%
“…A higher female to male sex ratio increases fertilization success and productivity (Maskill et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the chi-square test, the female and male tuna ratio is statistically in an unbalanced state. Understanding sex ratio is related to maintaining the sustainability of fish populations (Budd et al, 2015;Fryxell et al, 2015;Madenjian et al, 2016;Benevenuto et al, 2017;Maskill et al, 2017;Provoost et al, 2017). Therefore, it is expected that the ratio of male and female fish is balanced.…”
Section: Sex Ratio and Maturity Stages Of Gonadsmentioning
confidence: 99%